1990
DOI: 10.1111/j.1476-5381.1990.tb14641.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of myocardial enzyme release by ranolazine in a primate model of ischaemia with reperfusion

Abstract: In control anaesthetized baboons subjected to 30 min occlusion of the left anterior descending coronary artery, followed by 5.5 h reperfusion, total plasma levels for creatine kinase (CK) and lactate dehydrogenase (LDH) were markedly elevated in a time-related manner. In a second group of baboons pretreated 10min prior to ischaemia with ranolazine [(±+N{2,6-dimethyl-phenyl)-4[2-hydroxy-342-methoxyphenoxy)propyl]-1-piperazine acetamide dihydrochloride; RS43285-193] at 500pgkg-1 i.v., followed by continuous infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 7 publications
(6 reference statements)
0
26
0
Order By: Relevance
“…Ranolazine has demonstrated myocardial anti-ischaemic activity in a number of in vivo (Allely and Alps 1990;Allely et al 1993) and in vitro McCormack et al 1996) preparations from several different species. Initial clinical findings have suggested that ranolazine is an orally active agent potentially useful for angina pectoris therapy (Cocco et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Ranolazine has demonstrated myocardial anti-ischaemic activity in a number of in vivo (Allely and Alps 1990;Allely et al 1993) and in vitro McCormack et al 1996) preparations from several different species. Initial clinical findings have suggested that ranolazine is an orally active agent potentially useful for angina pectoris therapy (Cocco et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In an animal model, ranolazine increases myocardial blood flow (MBF), possibly because inhibition of late sodium current results in a decrease in left ventricular (LV) stiffness, which in turn decreases extravascular compressive forces on coronary microcirculation and thereby improves MBF (11)(12)(13)(14). Such an improvement in MBF is likely to contribute to the antianginal effects of ranolazine.…”
mentioning
confidence: 96%
“…Ranolazine has also been shown to be remarkably effective in preventing myocardial enzyme release in an intact primate model of ischaemia with reperfusion (Allely & Alps, 1990). It has been suggested that ranolazine may alleviate the symptoms of transient myocardial ischaemia by altering substrate utilization (Allely et al, 1987).…”
Section: Introductionmentioning
confidence: 99%